Immunogenicity and Clinical Efficacy Combined Vaccine against Diphtheria, Tetanus and Hepatitis B in Patients with Chronic Obstructive Pulmonary Disease - M. P. Kostinov; N. A. Kulakova; O. O. Magarshak; V. N. Borisova; V. B. Polishchuk; A. M. Kostinova; A. A. Ryzhov; A. M. Kostinov (Эпидемиология и вакцинопрофилактика)
The article presents the results of vaccination against diphtheria, tetanus and hepatitis B virus with the use of combined vaccine Bubo-M or a monovalent vaccine Hepatitis B in 120 patients with severe and medium chronic obstructive pulmonary disease (COPD) and 77 healthy people at the age 35 - 60 years. The lack of protective antibodies to diphtheria in patients with COPD was noted. The safety of immunization and the delayed production of post-vaccination antibodies to these infections were shown. The level of post-vaccination antibodies was the same as in healthy group after the administration of 3-rd dose both of the monovaccine and the combined one. During the year a clinical effect in reducing the number of exacerbations of the disease after a triple injection of the combined Bubo-M vaccine in patients with COPD was observed, comparable to that in patients with the combined use of the immunomodulator and hepatitis B vaccine. Moreover combined vaccination with immunomodulator led to normalization of level of the inflammatory mediators. Conclusion: Vaccination of patients with COPD with the use of the combined vaccine Bubo-M has both an advantages in clinical effect and the spectrum of anti-infection protection in comparison with the monovaccine against hepatitis